Warum nur arbeiten Kreative so gerne in der Stadt? Über die praktische Relevanz von Stadtaffinität für kreativ-wirtschaftliche Tätigkeiten. - Brake, Klaus (Taylor & Francis, 2015)
The "creative industry" displays a striking preference for the city. But what practical advantages does an urban working environment offer the creative industry in terms of successful economic activity? This study aims to answer that question by empirically researching the "creative fields" of product design and communications. Obvious advantages - such as short commuting distances, diversity, and interaction - point to interesting environmental qualities - such as physical proximity, density, anonymity, and openness - as ideal prerequisites, specifically for creative work - such as stimulation, feedback, and work-life balance. The complex urban environment acts not only as an inspirational backdrop for the creative, but also as a challenging arena in which to prove one's self. Additionally, it provides a motivational setting, which promotes the authenticity and identity of the creative individual and their product, especially with regard to the urban consumer, the context of use, and the particular demands made by that context.
Keywords: Standort; Stadtentwicklung; Stadtforschung; Innenstadt; Standortwahl; Stadtstruktur; Stadtraum; Wirtschaftsstruktur; Kreativwirtschaft; Kreativität; Arbeitsumgebung